Electromyographic activity of quadriceps and hamstrings of a professional football team during Bulgarian Squat and Lunge exercises - Navarro, E.; Chorro, D.; Torres, G.; Navandar, A.; Rueda, J.; Veiga, S. (Journal of Human Sport & Exercise, 2021)
The aim of this study was to analyse the quadriceps-hamstring coactivation in the lunge and Bulgarian squat exercises. A cross-sectional study design was applied to seventeen healthy professional football players. Muscular activity was measured using wireless surface electromyography (sEMG). The Maximum Voluntary Isometric Contraction was used to normalize the data. The muscle activation of each muscle belly was significantly different between the two exercises (F4.24 = 28.076, p < .001, partial Eta2 = .72). Activity in individual muscles varied in both the lunge (F4,24 = 49.315, p < .001,partial Eta2 = .89), and the Bulgarian squat (F4,24 = 28,076, p < .001,partial Eta2 = .82). The results showed no significant differences between the preferred and non-preferred legs of the participants (p > .05). In both the lunge and the Bulgarian squat, a significantly greater activation of the vastus medialis (VM) and the vastus lateralis (VL) muscles were found compared to the rectus femoris (RF) and biceps femoris (BF) and semitendinosus (ST). Muscles showed a greater activation during the Bulgarian squat compared to the lunge, but the hamstrings to quadriceps ratio was similar in both exercises (p > .05). The present work shows that the Bulgarian Squat exercise produces greater muscle activation than the Lunge exercise, whereas in both exercises there is a similar pattern of muscle activation. No differences were found between legs. If one wants to work specifically on strength development, the Bulgarian Squat would be a better option, as would be the case if one were to focus on synergistic work on the quadriceps and hamstrings, as the Bulgarian Squat exercise shows a higher H:Q ratio.